Photochemical Efficiency of Photosystem II in Inverted Leaves of Soybean [Glycine max (L.) Merr.] Affected by Elevated Temperature and High Light - Wang, Cong; Gu, Qiuli; Zhao, Lianjia; Li, Chunyan; Ren, Jintao; Zhang, Jianxin (Frontiers in Plant Science, 2022)
In summer, high light and elevated temperature are the most common abiotic stresses. The frequent occurrence of monsoon exposes the abaxial surface of soybean [Glycine max (L.) Merr.] leaves to direct solar radiation, resulting in irreversible damage to plant photosynthesis. In this study, chlorophyll a fluorescence was used to evaluate the functional status of photosystem II (PSII) in inverted leaves under elevated temperature and high light. In two consecutive growing seasons, we tested the fluorescence and gas exchange parameters of soybean leaves for 10 days and 15 days (5 days after recovery). Inverted leaves had lower tolerance compared to normal leaves and exhibited lower photosynthetic performance, quantum yield, and electron transport efficiency under combined elevated temperature and high light stress, along with a significant increase in absorption flux per reaction center (RC) and the energy dissipation of the RC, resulting in significantly lower performance indexes (PIABS and PItotal) and net photosynthetic rate (Pn) in inverted leaves. High light and elevated temperature caused irreversible membrane damage in inverted leaves, as photosynthetic performance parameters (Pn, PIABS, and PItotal) did not return to control levels after inverted leaves recovered. In conclusion, inverted leaves exhibited lower photosynthetic performance and PSII activity under elevated temperature and high light stress compared to normal leaves.